The Hellenistic settlements in Syria, the Red Sea Basin, and North Africa - Cohen, Getzel M. (The Joan Palevsky imprint in classical literature, 2006)
This authoritative and sweeping compendium, the second volume in Cohen's survey of the Greek settlements founded or refounded in the Hellenistic period, provides historical narratives references, citations, and commentaries on all the settlements in Syria, the Red Sea Basin, and North Africa from 323 to 28 B.C.E